Manajemen Anestesi pada Operasi Craniotomi Pasien Cedera Kepala Sedang Akibat Epidural Hematoma: Sebuah Laporan Kasus - Lailatut Toriqoh; Bambang eko (Medula, 2022)
Head injury is a cause of morbidity and mortality worldwide, can occur due to mechanical trauma either directly or indirectly that occurs due to impact, shock, blow or penetrating injury to the head that interferes with neurological function, namely physical, cognitive, psychosocial functioning temporarily. nor permanent. Epidural Hematoma (EDH) is the presence of an extra-axial collection of blood in the potential space between the internal tabula and the dura mater due to rupture of the bridging vein. A 16-year-old boy who is a referral from the Ryacudu Hospital Kotabumi came to the ER Abdul Moelok Hospital with a post-traffic accident that he fell from his motorbike about 7 hours before entering the hospital. The patient had decreased consciousness 10 minutes after the accident. Later, the patient regained consciousness and complained of headache and projectile vomiting. On physical examination, the general condition was moderate apatis consciousness, GCS E3V5M5, blood pressure 110/70 mmHg, pulse 78x/minute, respiration 20x/minute, axillary temperature 36.8 °C, body weight 45kg. On neurological examination, pupillary isocor, direct light reflex (+/+) and indirect light reflex (+/+). On examination of the head found a vulnus laseratum in the parietal region with a size of 7 cm x 0.1 cm which has been heacted. The patient underwent a craniotomy to evacuate the hematoma under general anesthesia and with due observance of the principles of neuroanesthesia during the surgical procedure.